Valuing meteorological services in resource-constrained settings: Application to smallholder farmers in the Peruvian Altiplano - Alexandra Brausmann; Moritz Flubacher; Filippo Lechthaler (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
Changing climate and weather patterns have resulted in reduced agricultural productivity in some parts of the world and put pressure on global food security. Availability and improved quality of meteorological information is seen as a potentially propitious means of adaptation to changing climate conditions. Forecasts of extreme weather events are especially valuable in resource-poor settings where climate-related vulnerability is high, such as for smallholder farmers in the developing world. In this paper we provide estimates of frost warnings valuation in the context of small-scale quinoa production in the Peruvian Altiplano. We first present a detailed contextual assessment of quinoa production in the study region based on agrometeorological and socio-economic data that was obtained through a representative farm household survey conducted in December 2016. Building on this assessment, we propose a stochastic life-cycle model, replicating the lifetime cycle of a quinoa-producing household, in order to derive a theoretical valuation of frost warnings. Calibrating the model to our data we provide estimates of potential frost-warning valuation which are in the range of 30-50 per household and year, depending on the forecast accuracy and agents' risk aversion. In a last step, using the observational data from the farm household survey, we show that access to existing meteorological services is empirically associated with avoided losses in agricultural production that amount to 18 per average household and per year. Our findings point to high climate vulnerabilities of smallholders in the Peruvian Altiplano and potentially large welfare gains from incorporating improved meteorological services into their decision-making process.
Keywords: C25; D81; H41; O13; Q12; Q16; Q51; 330; Valuation; meteorological information; uncertainty; agriculture; quinoa farming; climate change